Development of cooling system mechanism for photovoltaic module / Mohd Syahrul Asri Abdullah - Abdullah, Mohd Syahrul Asri (2014)
This thesis presents about the development of cooling system mechanism for photovoltaic module. Nowadays, solar energy is one of the most important sources among the renewable energies. One of the problems occur when using the photovoltaic is that low conversion efficiency of PV modules due to the heating of PV modules. This is because of the solar radiations that have been absorbed are not folly converting into electricity but parts of it are changed over into thermal energy. It is well known that the conversion efficiency decreases with the increase of PV modules surface temperature. Therefore, this project objective is to develop a workable prototype of cooling system mechanism that attached to the PV module. This system is designed by using Fritzing software. It is controlled by a microcontroller ATmega328p which it's programmed by using Arduino software.